Legal Protection of Citizens' Privacy Rights Based on the Principle of Jus - Arman, Zuhdi (KnE Social Sciences, 2025)
The development of digital technology has created serious challenges to the protection of citizens’ privacy rights. The rampant leakage and misuse of personal data by the public and private sectors shows the weakness of existing legal protection. Although Law Number 27 of 2022 concerning Personal Data Protection has been enacted, the effectiveness of its implementation is still in doubt, especially in ensuring justice for victims of privacy violations. This article analyzes the legal protection of privacy rights using the principle of justice approach, namely distributive, corrective, and procedural justice. The approach used is juridical-normative, complemented by case studies of personal data violations. The results of the study show that legal protection of privacy rights is still inadequate in substance. Therefore, the principle of justice needs to be used as the main foundation in the reconstruction of the legal system in the digital era.